Covid 19 Outbreak and Financial Statement Quality: Evidence from Central Java - Nurcahyono Nurcahyono; Fatmasari Sukesti; Alwiyah Alwiyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2021)
This study aims to analyze and find empirical evidence that the Covid 19 pandemic will affect the quality of financial reports and what factors affect the quality of government financial reports. The variables used in this study are competence, compliance with government accounting standards, external pressures, environmental uncertainty, internal control systems, and the quality of financial reports. The population of this study was accounting or finance staff who served in 48 SKPDs in the Central Java Provincial Government. The sampling technique used was simple random sampling, this sampling technique was chosen because the study population was homogeneous. Analysis of research data using the WarpPLS 7.0 application as well as used for hypothesis testing. The results show that competence, compliance with government accounting standards has a positive effect on the quality of financial reports, while external pressure has no effect and environmental uncertainty has a negative effect on the quality of financial reports. Internal control is able to strengthen the relationship between competency variables and compliance variables with the quality of financial reports and weaken the relationship between internal pressure variables and environmental uncertainty variables on the quality of local government financial reports. The implication of this research is that the quality of financial reports can be achieved when the work structure has good competence, complies with government accounting standards, is able to anticipate uncertainty and applies internal controls properly.